2015
DOI: 10.1542/peds.2014-2888
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Social Determinants of Health at Well Child Care Visits: A Cluster RCT

Abstract: OBJECTIVE: To evaluate the effect of a clinic-based screening and referral system (Well Child Care, Evaluation, Community Resources, Advocacy, Referral, Education [WE CARE]) on families' receipt of community-based resources for unmet basic needs. METHODS:We conducted a cluster randomized controlled trial at 8 urban community health centers, recruiting mothers of healthy infants. In the 4 WE CARE clinics, mothers completed a self-report screening instrument that assessed needs for child care, education, employm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
525
2
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 503 publications
(550 citation statements)
references
References 36 publications
12
525
2
11
Order By: Relevance
“…20 Many low-income families experience risks at multiple levels of this Hierarchy, risks that can have an undeniable impact on health and development. [22][23][24] Families confront issues related to food and housing insecurity at the base of the Hierarchy, as well as issues related to unemployment and lack of parenting support higher up on the Hierarchy. As we began to develop community interventions to address PPCC families' needs, Maslow's Hierarchy helped our team prioritize the risks we needed to focus on first and map them to appropriate interventions to more effectively help children reach their full potential.…”
Section: Organize and Prioritize Risks By Using Maslow's Hierarchy Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Many low-income families experience risks at multiple levels of this Hierarchy, risks that can have an undeniable impact on health and development. [22][23][24] Families confront issues related to food and housing insecurity at the base of the Hierarchy, as well as issues related to unemployment and lack of parenting support higher up on the Hierarchy. As we began to develop community interventions to address PPCC families' needs, Maslow's Hierarchy helped our team prioritize the risks we needed to focus on first and map them to appropriate interventions to more effectively help children reach their full potential.…”
Section: Organize and Prioritize Risks By Using Maslow's Hierarchy Ofmentioning
confidence: 99%
“…Studies have demonstrated that the "meaningful use" of the electronic health record includes screening for risks related to the SDH. 24,39,45,46 This integration of the SDH into the electronic health record also may facilitate an enhanced awareness of available community resources in ways that promote improved outcomes for patients and families. 42 Determining which risks to screen for may follow from an early needs assessment of commonly identified risks.…”
Section: Electronic Health Record Usementioning
confidence: 99%
See 1 more Smart Citation
“…While more research on the appropriate interventions to address these mechanisms is needed (29), research to date does indicate that providing services to address poverty in childhood does contribute to improved outcomes (19). Importantly, when healthcare providers are able to effectively identify the socio-environmental factors (including poverty) that place a child at risk for poor health outcomes, providers can effectively connect families to services that address those needs (30). Such interventions often need to target parenting behaviors known to be associated with poverty (29); whether changing caregivers addresses some of these issues for children entering nonparental care is not well understood.…”
Section: Poverty Nonparental Care and Healthmentioning
confidence: 99%
“…3,4 Primary care providers experience a sinking feeling when after the clinical encounter, their hand on the doorknob to leave the examination room, their patient adds 1 more reason for the visit-perhaps they lost their job, are unable to afford their medicine, or are about to be evicted from their home. Screening for social needs has proven valuable for certain age groups: children during well-child visits, 5 patients with chronic habits such as smoking, 6 and high-risk patients with complex chronic diseases. 7 The WellRx pilot cast a wider net, evaluating the feasibility of systematically screening for and addressing patients' social needs during every visit in busy general primary care settings.…”
mentioning
confidence: 99%